MODERNIZATION OF DIESEL ENGINES MANUFACTURED AT THE YAROSLAVL MOTOR WORKS - D. Mironov; V. Solomevich (Наука и техника)
The paper considers modernization of the Russian engines which are manufactured at the Yaroslavl Motor Works Factory and installed on towing trucks, drop-side trucks and «Masheka» auto-cranes designed on the basis of MAZ vehicles. The modernization will permit significantly  to increase power,  to decrease  fuel consumption, to reduce exhaust gas toxicity аnd engine noise level.